How Acquisition Entrepreneurs Influence the Sustainable Consolidation of Small to Medium-Sized Businesses and Economic Growth - Burks Jr, Leon (Digital Repository of Theses - SSBM Geneva, 2025)
This research investigates the influence of acquisition entrepreneurship on the sustainable consolidation of small- to medium-sized businesses and broader economic growth. Focusing on Acquisition Entrepreneurship (AE) and Entrepreneurship Through Acquisition (ETA), the study explores the evolving landscape of these entrepreneurial pathways. A qualitative methodology is employed, including an extensive literature review, in-depth case studies, and thematic analysis, to provide a comprehensive understanding of AE and ETA. The research begins by defining AE/ETA and highlighting their strategic advantages over traditional startup approaches. Subsequent chapters examine the sustainability of industry-specific mergers and acquisitions, emphasizing their role in maintaining business continuity and economic stability. Generational dynamics in business ownership are also analyzed, particularly the transition of businesses from Baby Boomers to Millennials, assessing the community and economic impacts of these shifts. The methodology section outlines the qualitative approach, detailing literature selection, criteria for case studies, and thematic analysis. By exploring these underexplored entrepreneurial pathways, the research aims to contribute to the broader understanding of how AE and ETA can drive sustainable business practices and economic growth.